Davčno obravnavanje pravih in nepravih tristranskih poslov v sistemu DDV - Pozvek, Maruša (Podjetje in delo, 2014)
Establishment of a single European economic area, based on the common market, is a primary reason for the introduction of the institute of tripartite transactions. Free movement of goods is one of the freedoms of the single market of the EU that allows successive sale of goods from the first seller to the last buyer, which is concluded between three taxpayers each from different country. Tripartite transaction is a subtype of the chain transaction. When taxpayers are each from a different EU Member State, we are dealing with genuine triangular transactions, for which we use simplification in order to facilitate the movement of goods within the EU and reduce administrative obligations. In terms of tax treatment triangular transactions are the most demanding. Especially problematic are quasi-triangular transactions in which one link in the chain is a natural person, the company that is one of the links in the chain is established outside the EU, or when the goods travel from the first country to the second and then to the third one. The quasi-triangular transactions for a combination of intra-EU exports and imports of goods demand appropriate tax analysis due to non-application of simplifications for those transactions, so tax solutions vary from case to case. In practice, the participants in the business often abuse the VAT identification numbers for unlawful purposes, such as various fraud and tax evasion.
Keywords: davek na dodano vrednost; davki; European Union; Evropska unija; izvoz; mednarodna trgovina; prosta trgovina; tax; uvoz